Algorithm of building UAV flight trajectories for static target surveillance - A. V. Markov; V. I. Simankov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
We describe an algorithm building UAV flight path for static targets surveillance. The algorithm provides a sub minimal path and takes into consideration limitation by the maximum turning radius.